HUBUNGAN KECANDUAN GAME ONLINE DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA TIM E-SPORT MOBILE LEGEND UPN VETERAN JAKARTA - Rangga Lunggah Fajar Nusantara (2022)
The COVID-19 pandemic has made people do more activities at home, making some people spend their time playing games using smartphones, especially for e-sports players where e-sports as a new sport based on electro-games are easily accessible in all places by players to practice in online game. When a person really cannot be separated from playing online games, it is said to be addicted to online games. Low back pain is pain related to stress or strain of the back muscles, tendons and ligaments caused by poor physical activity. The purpose of this study was to analyze the relationship between online game addiction and low back pain in the UPN Veteran Jakarta e-sports mobile legend team. This study uses a quantitative approach and a cross sectional research design. The sampling technique used was purposive sampling, which obtained a sample of 80 respondents. In this study, the Pearson correlation test obtained p value = 0.000 (<0.05) and correlation coefficient p = 0 , so online game addiction with low back pain has a moderate relationship. So, suggestions for the UPN Veteran Jakarta E-sports team when playing online games are to change your sitting position properly and it is recommended that after playing the game for a long time, you can take a break or stretch.